The nexus between globalization and ethnic identity: A view from below. (October 2019) - Ariely, Gal
While some studies have examined the impact of globalization on national identity 'from below', their findings are inconclusive, some arguing that national identity is less important for people in more globalized countries, others finding evidence to the contrary. Addressing and resolving some of the previous studies limitations, this article investigates the relationship between globalization and national identity with four cross-national surveys, using 149 national samples across 74 countries, inspecting whether country level of globalization impacts ethnic identity and whether globalization moderates between patriotism and ethnic identity. The findings indicate that although ethnic identity levels are lower in the more globalized than the less globalized countries, globalization has no differential effect on the strong and positive link between patriotism and ethnic identity.